Home blood glucose biosensors: a commercial perspective - Newman, Jeffrey D.; Turner, Anthony P. F. (Elsevier, 2005)
Twenty years on from a review in the first issue of this journal, this contribution revisits glucose sensing for diabetes with an emphasis on commercial developments in the home blood glucose testing market. Following a brief introduction to the needs of people with diabetes, the review considers defining technologies that have enabled the introduction of commercial products and then reviews the products themselves. Drawing heavily on the performance of actual instruments and publicly available information from the companies themselves, this work is designed to complement more conventional reviews based on papers published in scholarly journals. It focuses on the commercial reality today and the products that we are likely to see in the near future.
Keywords: Blood glucose monitors; Diabetes; Glucose biosensors; Alternate-site testing; Lancing; Medisense